Myopia Progression in Children: A Comparative Analysis of Pre-Pandemic and Pandemic Periods - Harsya Luthfi Anshari; Kemala Sayuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The COVID-19 pandemic brought about significant changes in children's lifestyles, including increased screen time and reduced outdoor activities due to school closures and lockdowns. These changes raised concerns about potential myopia progression in children. Methods: This study compared the spherical equivalent (SE) measurements of children aged 8-17 years from two time visits: one before the pandemic (September 2019 - February 2020) and one during the pandemic (March 2020 - February 2022). Data on family history of myopia, screen time, and outdoor activities were also collected. Paired t-tests were used to analyze the differences in SE between the two visits. Results: A total of 11 children participated in the study. The mean change in SE was -1.55 D, indicating a significant increase in myopia during the pandemic (p = 0.046). The average daily screen time was 201 minutes, while outdoor activity time was 42 minutes. Conclusion: The findings suggest a potential corelation between increased screen time, reduced outdoor activities, and myopia progression in children during the pandemic. It is crucial to encourage healthy visual habits, including limiting screen time and promoting outdoor activities, to mitigate the impact of the pandemic on children's vision.